Click-Chemistry Cross-Linking of Hyaluronan Graft Copolymers - Mario Saletti; Marco Paolino; Lavinia Ballerini; Germano Giuliani; Gemma Leone; Stefania Lamponi; Marco Andreassi; Claudia Bonechi; Alessandro Donati; Daniele Piovani; Alberto Giacometti Schieroni; Agnese Magnani; et al. (MDPI AG, 2022)
An easy and viable crosslinking procedure by click-chemistry (click-crosslinking) of hyaluronic acid (HA) was developed. In particular, the clickable propargyl groups of hyaluronane-based HA-FA-Pg graft copolymers showing low and medium molecular weight values were exploited in crosslinking by click-chemistry by using a hexa(ethylene glycol) spacer. The resulting HA-FA-HEG-CL materials showed an apparent lack of in vitro cytotoxic effects, tuneable water affinity, and rheological properties according to the crosslinking degree that suggests their applicability in different biomedical fields.